Pengenalan Komponen Elektronika Raspberry Pi Untuk Kalangan Siswa dan Siswi di Kembangan Utara - Lukman Medriavin Silalahi; Imelda Uli Vistalina Simanjuntak; Freddy Artadima Silaban; Setiyo Budiyanto; Dimas Jatikusumo; Muhammad Ikhsan; Agus Dendi Rochendi (Jurnal Abdimas ADPI Sains dan Teknologi, 2020)
Industry demand for skilled human resources presents a challenge for every school graduate to conduct various competency and skills training. So, the solution to meet industry challenges is a training on the application of science and technology for the community entitled "Introduction to the Raspberry Pi Electronic Components for Students in Kembangan Utara". The final output of this activity is to provide training and counseling on the Raspberry Pi module, in this case the design of a simple Water Irrigation system, using a water level detector as input information that will be processed and processed by the Raspberry Pi. The results of this community service activity were that students were introduced to a mini computer device called the Raspberry Pi and its application.